A Study of the Relationship Between Job Related Stress and Temporomandibular Disorders in Accountants Working in Jakarta - Saputra, Cindy Maura; Himawan, Laura Susanti; Tanti, Ira (UI Scholars Hub, 2016)
Stress is a known risk factor for Temporomandibular Disorders (TMD), however there are few studies of TMD in people who work in high stress jobs. Accounting is a profession known for its high levels of stress and expectation. Objective: The aim of this study is to investigate the relationship between the intensity and frequency of job related stress and the occurrence of TMD in accountants in Jakarta. Methods: A cross-sectional study, with ethics approval from the Ethical Committee of the Faculty of Dentistry, University Indonesia, was performed on 116 accountants aged 21 to 50, living in Jakarta. Subjects were asked to complete two questionnaires; the first was the Job Stress Survey questionnaire that examined the intensity and frequency of job related stress, and the second was the TMD Diagnostic Index, which assessed TMD prevalence. Results: Fisher’s exact test showed a significant relationship between the intensity of job related stress and the occurrence of TMD in accountants (p = 0.003). Chi-square tests showed a significant relationship between the frequency of job related stress and the occurrence of TMD in accountants (p = 0.032). Conclusion: There is a relationship between the intensity and frequency of job related stress, and the occurrence of TMD in accountants.